2014
DOI: 10.1007/s00217-014-2381-y
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes in espresso coffee: impact of preparation parameters

Abstract: The aim of the present study was to evaluate the effect of preparation conditions of espresso coffee (EC) on the diterpenes profile. ECs were prepared from roasted and ground (R&G) Arabica coffee and analyzed for the content of cafestol and kahweol by liquid-liquid extraction followed by HPLC-DAD, as well as their lipid content. The main variables in the present study were: the water quantity, the amount of coffee, the particle size, the percolation time, the water temperature and pressure.Average cafestol, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…The coffee ground was normally distributed with the lowest weight fractions for dimensions greater than 600 µm and lower than 180 µm, while the majority of the coffee ground was in the range of 250–400 µm, with mass fraction values between 32 ± 4.8% and 47.14 ± 14.14%. According to our results, Moeenfard et al reported a normal distribution but, in other cases, by using a laser diffraction system, a particle size distribution with a bimodal shape was observed showing a mass fraction of ∼2% for particles having sizes in the range of 50–100 µm . This difference is caused by the tendency of the finest particles (<100 µm) to aggregate into larger particles which cannot be resolved when using the sieve‐based method.…”
Section: Resultssupporting
confidence: 67%
“…The coffee ground was normally distributed with the lowest weight fractions for dimensions greater than 600 µm and lower than 180 µm, while the majority of the coffee ground was in the range of 250–400 µm, with mass fraction values between 32 ± 4.8% and 47.14 ± 14.14%. According to our results, Moeenfard et al reported a normal distribution but, in other cases, by using a laser diffraction system, a particle size distribution with a bimodal shape was observed showing a mass fraction of ∼2% for particles having sizes in the range of 50–100 µm . This difference is caused by the tendency of the finest particles (<100 µm) to aggregate into larger particles which cannot be resolved when using the sieve‐based method.…”
Section: Resultssupporting
confidence: 67%
“…For espresso, moka and French press coffee, the soluble lipids and solid material easily pass through the metal filter such as the diterpenes retained (RATNAYAKE et al, 1993). For espresso coffee, the diterpene levels are dependent on steam pressure (8 -12 bar) and coffee-to-water ratio (GROSS; JACCAUD; HUGGETT, 1997;MOEENFARD et al, 2015a;RATNAYAKE et al, 1993;SILVA et al, 2012). The pressure forces the oil inside the cells to migrate to the surface of coffee particles, where they are carried out by the hot water (MESTDAGH; GLABASNIA; GIULIANO, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Portuguese researchers from University of Porto (UP) approached the subject in four studies after noticing some gaps in the literature. The first one, by Moeenfard et al (2015a), studied the impact of espresso preparation parameters on diterpene profiles, using HPLC-DAD. The parameters evaluated were: water and coffee powder amount, particle size, percolation time, water temperature and pressure.…”
Section: The Diterpene Content Of Different Coffee Beveragesmentioning
confidence: 99%
“…Then, 2.5 mL of coffee brew was transferred to polyethylene tubes and left to cool for some minutes and subjected to LLE. Extraction of diterpene esters was performed in duplicate according to the developed and validated methodology described previously by Moeenfard et al . Briefly, coffee brews were extracted directly using 5 mL of diethyl ether.…”
Section: Methodsmentioning
confidence: 99%